Scientometric analysis of research on "remotely piloted aircraft": A research agenda for the construction industry. Issue 3 (8th October 2019) - Golizadeh, Hamed; Hosseini, M. Reza; Martek, Igor; Edwards, David; Gheisari, Masoud; Banihashemi, Saeed; Zhang, Jingxiao
Abstract : Purpose: Remotely piloted aircraft (RPA) systems have emerged as an established tool within the construction industry. Concurrent with this trend has been the rise in research on RPA, establishing this as a new field of study within the construction management domain. What is needed now is an assessment of the current state of research in this emerging discipline – its strengths and weaknesses – by which future research on RPA in construction may be guided. The purpose of this paper is to address this need. Design/methodology/approach: A total of 59 peer-reviewed journal articles covering RPAs within the construction domain were systematically reviewed using a mixed-methods approach, utilizing qualitative-scientometric analyses techniques. Findings: The results reveal a field of study in its fledgling stage, with a limited number of experts operating somewhat in isolation, from a limited number of institutions. Key publication outlets are identified, with the main focus of research being in the technical areas of remote sensing, photogrammetry and image processing. Practical implications: The study benefits researchers and industry practitioners alike. For researchers, the identified gaps reveal areas of high priority in future research. For construction companies, particularly small to medium-sized businesses, the study raises awareness of the latest developments and potential applicability of RPAs in the industry. Originality/value: The study exposes what is missing from current research: a broader consideration of organizational adjustments needed to accommodate RPA usage, economic analyses and impediments to wider acceptance.